The versatility of plectin in cancer: A pan-cancer analysis on potential diagnostic and prognostic impacts of plectin isoforms - ARĞA, KAZIM YALÇIN (My University, 2023)
Plectin, encoded by PLEC, is a cytoskeletal and scaffold protein with a number of unique isoforms that act on various cellular functions such as cell adhesion, signal transduction, cancer cell invasion, and migration. While plectin has been shown to display high expression and mislocalization in tumor cells, our knowledge of the biological significance of plectin and its isoforms in tumorigenesis remain limited. In this study, we first performed pathway enrichment analysis to identify cancer hallmark proteins associated with plectin. Then, a pan-cancer analysis was performed using RNA-seq data collected from the Cancer Genome Atlas (TCGA) to detect the mRNA expression levels of PLEC and its transcript isoforms, and the prognostic as well as diagnostic significance of the transcript isoforms was evaluated considering cancer stages. We show here that several tissue specific PLEC isoforms are dysregulated in different cancer types and stages but not the expression of PLEC. Among them, PLEC 1d and PLEC 1f are potential biomarker candidates and call for further translational and personalized medicine research. This study makes a contribution as a stride to unravel the molecular mechanisms underpinning plectin isoforms in cancer development and progression by revealing the potent plectin isoforms in different stages of cancer as potential early cancer detection biomarkers. Importantly, uncovering how plectin isoforms guide malignancy and particular cancer types by comprehensive functional studies might open new avenues toward novel cancer therapeutics.
Keywords: Tıp; Dahili Tıp Bilimleri; Tıbbi Genetik; Yaşam Bilimleri; Biyoteknoloji; Moleküler Biyoloji ve Genetik; Sağlık Bilimleri; Temel Bilimler; Medicine; Internal Medicine Sciences; Medical Genetics; Life Sciences; Biotechnology; Molecular Biology and Genetics; Health Sciences; Natural Sciences; BİYOTEKNOLOJİ VE UYGULAMALI MİKROBİYOLOJİ; Mikrobiyoloji; Yaşam Bilimleri (LIFE); GENETİK VE KALITIM; BIOTECHNOLOGY & APPLIED MICROBIOLOGY; MICROBIOLOGY; Life Sciences (LIFE); GENETICS & HEREDITY; MOLECULAR BIOLOGY & GENETICS; Genetik (klinik); Uygulamalı Mikrobiyoloji ve Biyoteknoloji; Moleküler Tıp; Moleküler Biyoloji; Genetik; Genetics (clinical); Applied Microbiology and Biotechnology; Molecular Medicine; Molecular Biology; Genetics; plectin; plectin isoforms; carcinogenesis; prognostic biomarker; diagnostic biomarker; personalized medicine; INTERMEDIATE-FILAMENT; CARCINOMA-CELLS; EXPRESSION; INVASION; MUSCLE; SKIN; INVADOPODIA; DISRUPTION; COMPLEXITY; INTEGRITY